If it's not what You are looking for type in the equation solver your own equation and let us solve it.
2+8x=9x-4
We move all terms to the left:
2+8x-(9x-4)=0
We get rid of parentheses
8x-9x+4+2=0
We add all the numbers together, and all the variables
-1x+6=0
We move all terms containing x to the left, all other terms to the right
-x=-6
x=-6/-1
x=+6
| 9x-3=16x-8 | | (-4x^2)(2x-3)^(-4)=0 | | 4b=7b-24 | | 55-3x=28 | | x(4x+5)-8=0 | | 9x-27=16x-32 | | 3b+2.5=5.5+b | | 30x-3+20x-1+11x+1=180 | | -4/7y-8/3=-5/2 | | 3w-11=10 | | 6(5x+8)=230 | | 16-0.50x=12 | | -35m+24=186 | | 40=1/3x-8 | | -7x+23=-19 | | 8(y+2)+3=2(3y-4)-4 | | 22×+100=25x+100 | | -4(x+2)=-(x+2) | | 3+5n=5n+10-4 | | x+180=100 | | -4(8+6x)=40 | | x(x-10)+40=0 | | 0.04-0.01(x+2)=0.02(2-x) | | x+64+120=180 | | -6y+3=-3y−6 | | -4n-6(4n+3)=-n+3(-6n-3) | | 2x+3(1.5)=-1 | | -4v+-12=-12-4v | | 9(x+5)-3x-2=8x+31 | | 8x+-28=x | | -74+9x=4x+81 | | 2-5x=58 |